Modernist Disavowal - Stephen ROSS (E-REA)
This paper argues that the psychological mechanism of disavowal is at the heart of modernist conceptions of difference from the Victorians. It identifies the focal point of this disavowal in the overt repudiation of spiritualism and spectrality in key pronouncements by Joseph Conrad and Virginia Woolf. By reading those pronouncements closely, and comparing them to the use of spectrality and spiritualism in these writers’ novels, this paper argues that these key foundational figures of literary modernism enact a powerful case of disavowal. Though they explicitly deplore the use of the supernatural, Conrad and Woolf rely upon it in their fiction. This specific dual disavowal – of the Victorian precedent and of a lingering supernaturalism in their own work – is not just limited to Conrad and Woolf, but, I argue, informs the larger means by which the modernists strove to understand and articulate their break with the Victorians. Disavowal of the supernatural stands at the origin of modernist self-conception, anchoring the challenge to “make it new” directly in a matrix of ethico- aesthetic concerns.